Legal Consciousness and Legal Culture in Society Increase - Jamoliddinovich, Sobirov Mukhsinjon (European Journal of Life Safety and Stability (2660-9630), 2021)
Raising the legal awareness and legal culture in the society is one of the most important conditions for ensuring the rule of law and strengthening the rule of law.